Global prevalence and characteristics of non-suicidal self-injury between 2010 and 2021 among a non-clinical sample of adolescents: A meta-analysis - Xiao, Qingqing; Song, Xiaozhen; Huang, Lijuan; Hou, Dandan; Huang, Xuehua (Frontiers in Psychiatry, 2022)
Background: We meta-analyzed the global prevalence of NSSI and prevalence of NSSI characteristics in a nonclinical sample of adolescents between 2010 and 2021. Methods: A systematic search for relevant articles published from January 1, 2010 to June 30, 2021 was performed within the scholarly database search engines of CBM, CNKI, VIP, Wanfang, PubMed, Web of Science, PsycINFO, and Embase. The global prevalence of NSSI was calculated based on the random-effects model. Subgroup analyses were performed to compare the prevalence according to sex, living place, smoking or drinking history, and family structure. Results: Sixty-two studies involving 264,638 adolescents were included. The aggregate prevalence of NSSI among a nonclinical sample of adolescents was similar between over a lifetime (22.0%, 95% CI 17.9-26.6) and during a 12-month period (23.2%, 95% CI 20.2-26.5). Repetitive NSSI was more common than episodic NSSI (20.3 % vs. 8.3%) but the frequency of mild injury (12.6%) was similar to that of moderate injury (11.6%). Multiple-method NSSI occurred slightly more often compared than one-method NSSI (16.0% vs. 11.1%). The top three types of NSSI in adolescents were banging/hitting (12.0%, 95% CI 8.9-15.9), pinching (10.0%, 95% CI 6.7-14.8), and pulling hair (9.8%, 95% CI 8.3-11.5), and the least common type was swallowing drugs/toxic substances/chemicals (1.0%, 95% CI 0.5-2.2). Subgroup analyses showed that being female, smoking, drinking, having siblings, and belonging to a single-parent family may be linked to higher prevalence of NSSI. Conclusions: This meta-analysis found a high prevalence of NSSI in nonclinical sample of adolescents, but there are some changes in severity, methods and reasons. Based on the current evidence, adolescents in modern society are more inclined to implement NSSI behavior by a variety of ways, which usually are repetitive, and moderate and severe injuries are gradually increasing. It is also worth noting that adolescents with siblings or in single-parent families are relatively more likely to implement NSSI behavior due to maladjustment to the new family model. Future research needs to continue to elucidate the features and risk factors of NSSI so as to intervene in a targeted way. Keywords: adolescents, non-suicidal self-injury, prevalence, characteristics, meta-analysis